2016
DOI: 10.1055/s-0041-111504
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Colposcopically Guided Diagnostic Methods for the Detection of Cervical Intraepithelial Neoplasia

Abstract: !Introduction: Many factors can affect the accuracy of colposcopically guided biopsy, endocervical curettage (ECC) and differential cytology, all of which are standard, minimally invasive procedures used to detect cervical intraepithelial neoplasia. Method: All conizations carried out between 2007 and 2013 in the gynecological department of Hannover Medical School were retrospectively reviewed. The agreement between colposcopic diagnosis and histology was evaluated retrospectively. The analysis included 593 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
1
15
1
Order By: Relevance
“…1 Recent studies have shown suboptimal sensitivities of colposcopy with high inter-observer variation 2,3 and ability to correctly diagnose cervical dysplasia positively correlated with the number of biopsies taken. [4][5][6] To avoid under-diagnosis of cervical intraepithelial neoplasia (CIN), the Danish national guidelines on cervical dysplasia 7 recommend that four biopsies are taken in every woman who undergoes colposcopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Recent studies have shown suboptimal sensitivities of colposcopy with high inter-observer variation 2,3 and ability to correctly diagnose cervical dysplasia positively correlated with the number of biopsies taken. [4][5][6] To avoid under-diagnosis of cervical intraepithelial neoplasia (CIN), the Danish national guidelines on cervical dysplasia 7 recommend that four biopsies are taken in every woman who undergoes colposcopy.…”
Section: Introductionmentioning
confidence: 99%
“…17 Using a standard colposcope the agreement rate between histological diagnosis of colposcopy-directed biopsies (CDB) and histological diagnosis of conization specimens have been found to vary between 45% 18 and 89.6%. 5,[19][20][21][22] To the best of our knowledge, no study has compared the histological diagnosis of the biopsy/ies taken with the DSI colposcope to the histological diagnosis of the conization specimen.…”
Section: Introductionmentioning
confidence: 99%
“…19 The accuracy of colposcopy guided biopsy appears to increase when three biopsy specimens were taken and was particularly high for younger patients. 20 In this study, only fifteen premalignant cases and three cervical cases were detected out of 168 colposcopy guided procedures. Colposcopy, the single and irreplaceable second-level procedure for triage of cervical abnormalities, is challenged to match the today's screening tests, especially in view of the extended intervals that increase the risks for patients with missed disease.…”
Section: Discussionmentioning
confidence: 93%
“…Which was similar to other studies. This is due to the inflammatory and premalignant lesions of the cervix (16,24,25).…”
Section: Discussionmentioning
confidence: 99%